Comparative study by DFT method of physical properties of monolayer and bulk InX (X=P, As and Sb) - Hamza Imtki; El Houssine Atmani; Nejma Fazouan; Mustapha Madi (Results in Surfaces and Interfaces)
In this work, we investigated and compared the physical properties of planar monolayer and bulk structures of InX (X=P, As, and Sb) materials using density functional theory (DFT). The PBE-sol approximation is used for structural properties and mBJ one for electronic and optical properties. The results show that the lattice parameters of planar monolayers are greater than those of the corresponding bulk, while the In-X bond length is reduced. The band gaps are direct in bulk structures, whereas they become indirect in planar monolayers. Going from bulk to monolayer, we notice an increase in gap energies of 0.46, 0.53, and 0.34 eV for InP, InAs, and InSb, respectively. This increase is attributed to quantum size effects. The optical results show a high transparency for planar monolayers, which reaches 96% compared to bulk structures, which do not exceed 60%. According to our results, these compounds could serve as promising candidates for the development of future optoelectronic devices.